Preserving Cultural Identity Through Tahlilan: Strengthening Social Solidarity in Madura - Jailani, Mohammad (Jurnal Sosiologi Reflektif, 2024)
The tahlilan tradition in Madura serves not only as a religious ritual but also as a significant social and cultural mechanism that strengthens communal bonds. In the context of Madura, tahlilan goes beyond prayer, representing solidarity, empathy, and social cohesion among community members. This study aims to analyze how tahlilan influences social solidarity and harmony within Madurese society, focusing on its role in community integration and the maintenance of social ties. A qualitative case study method was employed, involving interviews with local religious leaders, community figures, and participants in the tahlilan rituals, along with observations of religious practices in Pasean, Pamekasan. The results show that tahlilan plays a crucial role in reinforcing collective identity and social harmony in Madura. It fosters a sense of belonging and mutual support across social classes, while also serving as a mechanism for collective grieving and emotional expression. However, financial pressures related to hosting tahlilan can lead to social strain, particularly among lower-income families. This study highlights the cultural significance of tahlilan and its impact on social dynamics but acknowledges that further research is needed to explore economic challenges and evolving practices in different socio-economic contexts. Tradisi tahlilan di Madura tidak hanya berfungsi sebagai ritual keagamaan, tetapi juga sebagai mekanisme sosial dan budaya yang memperkuat ikatan komunal. Dalam konteks Madura, tahlilan melampaui doa, mencerminkan solidaritas, empati, dan kohesi sosial di antara anggota masyarakat. Penelitian ini bertujuan untuk menganalisis bagaimana tahlilan memengaruhi solidaritas sosial dan harmoni dalam masyarakat Madura, dengan fokus pada peran tradisi ini dalam integrasi komunitas dan pemeliharaan hubungan sosial. Metode yang digunakan adalah studi kasus kualitatif, melibatkan wawancara dengan tokoh agama, tokoh masyarakat, dan peserta tahlilan, serta observasi langsung terhadap praktik keagamaan di Pasean, Pamekasan. Hasil penelitian menunjukkan bahwa tahlilan berperan penting dalam memperkuat identitas kolektif dan harmoni sosial di Madura. Tradisi ini mendorong rasa memiliki dan saling mendukung di berbagai lapisan masyarakat, serta menjadi mekanisme untuk meredakan duka bersama. Namun, tekanan finansial terkait pelaksanaan tahlilan dapat menimbulkan beban sosial, terutama bagi keluarga berpenghasilan rendah. Penelitian ini menekankan pentingnya tahlilan secara budaya dan pengaruhnya terhadap dinamika sosial, namun diperlukan penelitian lebih lanjut untuk mengeksplorasi tantangan ekonomi dan perubahan praktik dalam konteks sosial-ekonomi yang berbeda.